Plasma Kallikrein-Kinin System as a VEGF-Independent Mediator of Diabetic Macular Edema - Kita, Takeshi (Diabetes, 2015)
This study characterizes the kallikrein-kinin system in vitreous from individuals with diabetic macular edema (DME) and examines mechanisms contributing to retinal thickening and retinal vascular permeability (RVP). Plasma prekallikrein (PPK) and plasma kallikrein (PKal) were increased twofold and 11.0-fold (both P < 0.0001), respectively, in vitreous from subjects with DME compared with those with a macular hole (MH). While the vascular endothelial growth factor (VEGF) level was also increased in DME vitreous, PKal and VEGF concentrations do not correlate (r = 0.266, P = 0.112). Using mass spectrometry–based proteomics, we identified 167 vitreous proteins, including 30 that were increased in DME (fourfold or more, P < 0.001 vs. MH). The majority of proteins associated with DME displayed a higher correlation with PPK than with VEGF concentrations. DME vitreous containing relatively high levels of PKal and low VEGF induced RVP when injected into the vitreous of diabetic rats, a response blocked by bradykinin receptor antagonism but not by bevacizumab. Bradykinin-induced retinal thickening in mice was not affected by blockade of VEGF receptor 2. Diabetes-induced RVP was decreased by up to 78% (P < 0.001) in Klkb1 (PPK)-deficient mice compared with wild-type controls. B2- and B1 receptor–induced RVP in diabetic mice was blocked by endothelial nitric oxide synthase (NOS) and inducible NOS deficiency, respectively. These findings implicate the PKal pathway as a VEGF-independent mediator of DME.